4x+7=2-3x

Simple and best practice solution for 4x+7=2-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+7=2-3x equation:


Simplifying
4x + 7 = 2 + -3x

Reorder the terms:
7 + 4x = 2 + -3x

Solving
7 + 4x = 2 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
7 + 4x + 3x = 2 + -3x + 3x

Combine like terms: 4x + 3x = 7x
7 + 7x = 2 + -3x + 3x

Combine like terms: -3x + 3x = 0
7 + 7x = 2 + 0
7 + 7x = 2

Add '-7' to each side of the equation.
7 + -7 + 7x = 2 + -7

Combine like terms: 7 + -7 = 0
0 + 7x = 2 + -7
7x = 2 + -7

Combine like terms: 2 + -7 = -5
7x = -5

Divide each side by '7'.
x = -0.7142857143

Simplifying
x = -0.7142857143

See similar equations:

| 4x+8=34 | | -4x^3+6x^2-5x-2= | | ln(x+1)-lnx+ln(x^2)=1 | | (6x^4+5x^3-4)-(7x^2-8x+6)= | | (2y^3+4y)-(-2y^3-5y+4)= | | -3(x-1)-6=0 | | 2(4a-3)-(2a+5)=10 | | (2z^7-6z^3+8)+(8z^6+2z^3-6z)= | | 11ab+3b^2-6ab+6b^2-13= | | x^6-8x^5+7x^6-8x^5+8= | | 4x+6=-30 | | 5x+6=-109 | | 2x^3-15x-7=0 | | w^2+3w-18= | | 164-7x=38x+19 | | 13-7x=85-21x | | 3n-2=n+14 | | 5x=4x-3x+14 | | -3,2n+4,8=5 | | x+x^3=20 | | 2x-5=x+6 | | (X^2-6)=45 | | 35-2x=7x+21 | | 4-3i=x+12yi | | 7x-4y+8.04-2.7x=5y-0.8x+2 | | 3(2x-15)=4(x+1) | | 3(2x-15)=4(4x+1) | | 2x+y-x+4yi=-1+13i | | 3(2x-15)=4(4+1) | | 5x+3yi=15+i | | 15+-3i+3iy+2x+5y=0 | | y^3-y^2+2y-2=0 |

Equations solver categories